Alkane wax oil hydrocracking / isomerization catalyst and its preparation method and application
By using amorphous silicon-aluminum and alumina support to load a single metal element catalyst, the problems of low selectivity and high catalyst cost of distillate oil in the prior art are solved, and efficient hydrocracking is achieved and safety risks are reduced.
Patent Information
- Application Number
- CN202411743267.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-04-04
AI Technical Summary
In the prior art, the intermediate distillate oil of Fischer-Tropsch wax oil hydrocracking has low selectivity and high catalyst metal content, resulting in high preparation cost, poor metal dispersion, high metal vulcanization process cost and high safety risks.
Amorphous silicon aluminum and alumina are used as support and a single metal element (such as cobalt or nickel) is supported as active metals, and the catalyst is prepared by activation of hydrogen atmosphere, avoiding the vulcanization process.
It improves the selectivity of distillate oil, reduces catalyst production and operation costs, reduces safety risks, and improves the overall economic benefits of hydrogen refueling devices.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of coal chemical industry, and in particular to an alkane wax oil hydrocracking / isomerization catalyst and a preparation method and application thereof. Background Art
[0002] The technology of converting CO and H into long-chain hydrocarbons through Fischer-Tropsch synthesis is one of the effective means to solve the current shortage of petroleum raw materials. In the low-temperature Fischer-Tropsch synthesis products, the content of heavy distillate oil and heavy wax is high, and it is mainly normal hydrocarbons. It is necessary to produce more high-value low-freezing point diesel through hydrogenation modification (cracking, isomerization). Compared with the traditional hydrocracking raw material VGO, Fischer-Tropsch wax has a simple structure, mainly composed of normal alkanes and a small amount of isoalkanes, and has the characteristics of no aromatics, no residual carbon, no sulfur and no nitrogen, and a wide distillation range, with a final distillation point of 800°C. Therefore, Fischer-Tropsch wax is relatively easier to crack, and the life of the cracking catalyst is longer.
[0003] The prior art discloses a hydrocracking catalyst for producing diesel from Fischer-Tropsch wax, which uses Y zeolite, tungsten oxide or molybdenum oxide, oxide, aluminum oxide or silicon-aluminum mixture to prepare a catalyst with a specific surface area of 250-400m 2 / g, a hydrocracking catalyst with a pore volume of 0.3-0.7ml / g and a TPD acidity of 0.75-1.5mmol / g.
[0004] The prior art also discloses a Fischer-Tropsch wax hydrocracking catalyst, which contains columnar soapstone, alumina and a hydrogenation active metal component, wherein the active metals used are molybdenum, tungsten and nickel.
[0005] Most of the catalysts developed for the hydrocracking of Fischer-Tropsch wax oil above follow the idea of traditional petroleum-based wax oil hydrogenation, using bimetallic as active metal, which often needs to be made active for hydrogenation through a sulfurization process; the bimetallic element sulfurization process is used to reduce the risk of catalyst sulfur poisoning, improve the activity of the catalyst and diesel yield. However, the sulfurization process not only increases production costs, but also the catalyst manufacturing cost is high, which increases the operating cost and safety risk of the hydrogenation unit, and reduces the overall efficiency of the hydrogenation unit. Summary of the invention
[0006] The main purpose of the present application is to provide an alkane wax oil hydrocracking / isomerization catalyst and its preparation method and application, so as to solve the problems in the prior art of low selectivity for intermediate distillate oil in Fischer-Tropsch wax oil hydrocracking, high catalyst metal content resulting in high preparation cost, poor metal dispersion, high metal sulfidation process cost and high safety risk.
[0007] In order to achieve the above-mentioned purpose, according to one aspect of the present application, there is provided an alkane wax oil hydrocracking / isomerization catalyst, the catalyst comprising a carrier and an active metal; the active metal is loaded on the inner and outer surfaces of the pores of the carrier; wherein the carrier is composed of amorphous silica-alumina and alumina; the active metal is selected from a metal element in Group VIII.
[0008] Furthermore, the active metal is cobalt or nickel.
[0009] Furthermore, the loading amount of the active metal on the catalyst is 3 wt% to 30 wt% in terms of oxide, preferably 5 wt% to 20 wt%.
[0010] Furthermore, the weight of the amorphous silicon aluminum is 5% to 95% of the weight of the carrier, and preferably 60% to 80%.
[0011] Furthermore, the weight of the aluminum oxide is 5% to 95% of the weight of the carrier; preferably 20% to 40%.
[0012] According to the second aspect of the present application, the preparation method of the above-mentioned alkane wax oil hydrocracking / isomerization catalyst comprises the following steps:
[0013] Step S1: mixing amorphous silicon aluminum powder, a binder, and a sol, drying, and calcining I to obtain a catalyst carrier;
[0014] Step S2: immersing the catalyst carrier in a liquid containing an active metal compound and an organic complexing agent, drying and calcining II to obtain a catalyst; wherein the active metal element in the active metal compound is selected from a metal element in Group VIII;
[0015] Step S3: activating the catalyst in a hydrogen atmosphere to obtain an active catalyst.
[0016] Furthermore, the weight ratio of amorphous silica-alumina powder, binder and sol is (60-90):(20-40):(10-40); wherein the mass concentration of the sol is 0.01-10wt%, preferably 0.2-0.5%.
[0017] Furthermore, the molar ratio of the organic complexing agent to the active metal element is (0.1-2):1.
[0018] Furthermore, the weight ratio of the catalyst carrier to the active metal compound is (62-96):(15-151), preferably (74-93):(25-101).
[0019] Furthermore, the active metal element is cobalt or nickel.
[0020] Further, the active metal compound is selected from at least one of cobalt nitrate, cobalt chloride and cobalt sulfate, or the active metal compound is selected from at least one of nickel nitrate, nickel sulfate, nickel oxide and basic nickel carbonate.
[0021] Furthermore, the organic complexing agent is selected from at least one of ethylenediaminetetraacetic acid, citric acid, tartaric acid and lactic acid.
[0022] Furthermore, the pore volume of amorphous silicon aluminum powder is 1.0-2.0 mL / g, and the specific surface area is 400-600 m 2 / g, average pore size ≥10nm.
[0023] Furthermore, the binder is pseudo-boehmite.
[0024] Furthermore, the pore volume of pseudo-boehmite is 0.4-1.0 mL / g, and the specific surface area is 150-300 m 2 / g, average pore size ≥9nm.
[0025] Furthermore, the sol agent is selected from one or more of nitric acid, hydrochloric acid, acetic acid and citric acid; preferably nitric acid.
[0026] Furthermore, the specific process of step S1 includes: kneading amorphous silicon aluminum powder, a binder and a sol agent, extruding, drying I, and calcining I to obtain a catalyst carrier;
[0027] The conditions of drying I include: drying temperature of 100 to 300° C. and drying time of 0.5 to 24 hours.
[0028] Furthermore, the drying temperature is 150-200° C., and the drying time is 2-6 hours.
[0029] Furthermore, the conditions for calcining I include: a calcining temperature of 300 to 600° C. and a calcining time of 0.5 to 24 h.
[0030] Furthermore, the calcination temperature is 400-600° C., and the calcination time is 2-6 hours.
[0031] Furthermore, the specific process of step S2 includes: impregnating the catalyst carrier in an impregnation solution containing an active gold compound, drying II, and calcining II to obtain a catalyst;
[0032] The conditions of drying II include: drying temperature of 100-300° C., and drying time of 0.5-24 h; more preferably, drying temperature of 150-200° C., and drying time of 2-6 h.
[0033] Furthermore, the conditions of calcination II include: a calcination temperature of 300 to 600° C. and a calcination time of 0.5 to 24 hours.
[0034] Furthermore, the calcination temperature is 400-600° C., and the calcination time is 2-6 hours.
[0035] Furthermore, the activation conditions in step S3 include: hydrogen partial pressure of 0.1 to 8 MPa, reaction temperature of 200 to 600° C., and reaction time of 1 to 48 h.
[0036] Furthermore, the hydrogen partial pressure is 0.1-1 MPa, the reaction temperature is 300-500° C., and the reaction time is 4-24 h.
[0037] According to the third aspect of the present application, there is provided the use of the above catalyst or the catalyst obtained by the above method in the hydrocracking reaction of Fischer-Tropsch wax oil.
[0038] By applying the technical solution of the present application, a catalyst for hydrocracking / isomerization of alkane wax oil and a preparation method thereof are provided. The catalyst uses amorphous silicon-alumina with high pore volume and high specific surface area as the main component of the carrier, and loads a single metal element as the metal active center. There is no need to load multiple metal elements. The catalyst can be reduced in a hydrogen atmosphere to increase the activity of the catalyst and improve the selectivity of the target product. The catalyst is particularly suitable for hydrocracking of Fischer-Tropsch wax oil, can reduce the catalyst production cost, reduce the catalyst operating cost, increase the selectivity of the middle distillate oil, and improve the overall economic benefits of the hydrogenation unit. DETAILED DESCRIPTION
[0039] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below in conjunction with the embodiments.
[0040] Most of the catalysts developed for the hydrocracking treatment of Fischer-Tropsch wax oil in the prior art use bimetallic elements as active metals, which require a bimetallic element sulfidation process. The use of such catalysts not only increases production costs, but also the catalyst manufacturing cost is relatively high, thereby increasing the operating cost and safety risk of the hydrogenation unit and reducing the overall efficiency of the hydrogenation unit.
[0041] According to one aspect of the present application, a alkane wax oil hydrocracking / isomerization catalyst is provided, which includes a carrier and an active metal; the active metal is loaded on the inner and outer surfaces of the pores of the carrier; wherein the carrier is composed of amorphous silica-alumina and alumina; and the active metal is selected from a metal element in Group VIII.
[0042] The above-mentioned catalyst of the present application uses amorphous silicon-alumina with high pore volume and high specific surface area as the main component of the carrier, loads a single metal element as the metal active center, does not need to load multiple metal elements, has good selectivity, and is particularly suitable for Fischer-Tropsch synthesis wax oil hydrocracking; the use of this catalyst can reduce the catalyst production cost, increase the selectivity of middle distillate oil, and improve the overall economic benefits of the hydrogenation unit.
[0043] In some embodiments, the active metal of the catalyst is cobalt or nickel; the weight of the active metal loaded on the catalyst is 3% to 30% in terms of oxide; for example, 5wt% to 20wt%; for example, any value among 3%, 5%, 8%, 10%, 13%, 15%, 18%, 20%, 23%, 25%, 28%, 30% or any range between two values.
[0044] In some embodiments, the mass content of SiO2 in the amorphous silica-alumina in the catalyst carrier is 50-80%, the pore volume of the amorphous silica-alumina is 1.0-2.0 mL / g, and the specific surface area is 400-600 m 2 / g, average pore size ≥10nm; for example, pore volume is any value among 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0mL / g or any range between two values; specific surface area is 400, 450, 500, 550, 600m 2 / g or any range between the two; the pore volume of alumina is 0.4-1.0mL / g, and the specific surface area is 150-300m 2 / g, average pore size ≥ 9nm; for example, pore volume is selected from any value among 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0mL / g or any range between two values; specific surface area is selected from 150, 200, 250, 300m 2 / g, or any range of values between them.
[0045] The present application selects a carrier with the above-mentioned high pore volume and high specific surface area. More pores and surface area can allow more active metals to be dispersed on the carrier, which helps to improve the activity of the catalyst; it also provides more reaction sites for the reactants, improving the reaction efficiency; it can better evenly disperse the active metals, reduce the aggregation of active metals, and help improve the stability and service life of the catalyst; the higher pore volume can accommodate more reaction materials, increase the capacity of hydrogen, and reduce the rate of catalyst coking. The larger pore size is conducive to the mass and heat transfer of materials, increases the diffusion rate, and reduces the probability of secondary cracking.
[0046] In some embodiments, the weight of amorphous silicon aluminum is 5% to 95% of the weight of the support, such as 60% to 80%, such as any value in 5%, 10%, 20%, 30%, 40%, 50%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, or any range between two values. The weight of aluminum oxide is 5% to 95% of the weight of the support, such as 20% to 40%; such as any value in 5%, 10%, 20%, 30%, 40%, 50%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, or any range between two values.
[0047] The present application adopts amorphous silicon aluminum and aluminum oxide in the above-mentioned proportion to form a carrier. Aluminum oxide can effectively improve the mechanical strength of the catalyst carrier on the one hand, and increase the porosity of the catalyst carrier on the other hand, thereby further increasing the specific surface area of the catalyst, which is beneficial to improving the efficiency of the catalytic reaction, improving the dispersion of the active metal, improving the thermal stability of the catalyst, and preventing the loss of the active metal.
[0048] According to the second aspect of the present application, a method for preparing the above-mentioned alkane wax oil hydrocracking / isomerization catalyst is provided, and the method comprises the following steps:
[0049] Step S1: mixing amorphous silicon aluminum powder, a binder, and a sol, drying, and calcining I to obtain a catalyst carrier;
[0050] Step S2: immersing the catalyst carrier in a liquid containing an active metal compound and an organic complexing agent, drying and calcining II to obtain a catalyst; wherein the active metal element in the active metal compound is selected from a metal element in Group VIII;
[0051] Step S3: activating the catalyst in a hydrogen atmosphere to obtain an active catalyst.
[0052] The catalyst prepared by the above method in the present application is composed of amorphous silica-alumina, alumina, and active metal oxides; the catalyst is particularly suitable for Fischer-Tropsch wax oil hydrocracking, can reduce the catalyst production cost, reduce the catalyst operation cost, increase the selectivity of middle distillate oil, and improve the overall economic benefits of the hydrogenation unit.
[0053] In some embodiments, the weight ratio of amorphous silica aluminum powder, adhesive and sol is (60-90):(20-40):(10-40); wherein the mass concentration of the sol is 0.01-10wt%, preferably 0.2-0.5%; for example, the mass ratio of amorphous silica aluminum powder is any value among 60, 65, 70, 75, 80, 85, 90 or a range value between any two of them; the mass ratio of the adhesive is any value among 20, 25, 30, 35, 40 or a range value between any two of them; the weight ratio of the sol is any value among 10, 15, 20, 25, 30, 35, 40 or a range value between any two of them.
[0054] In some embodiments, the molar ratio of the organic complexing agent to the active metal element is (0.1-2):1; wherein the active metal element is cobalt or nickel; the active metal compound is selected from at least one of cobalt nitrate, cobalt chloride and cobalt sulfate, or the active metal compound is selected from at least one of nickel nitrate, nickel sulfate, nickel oxide and basic nickel carbonate; the organic complexing agent is selected from at least one of ethylenediaminetetraacetic acid, citric acid, tartaric acid and lactic acid.
[0055] The organic complexing agent used in the present application is hydrolyzed in an aqueous solution and can form a multi-coordinated complex with Ni ions in the metal impregnation solution. The formation of the complex reduces the agglomeration of metal particles in the pores and surface of the carrier and improves the dispersibility of the metal. At the same time, since the Ni ions in the impregnation solution preferentially bind to the acidic sites in the pores to form chemical bond adsorption, the addition of the complexing agent can reduce the bonding force between Ni and the carrier, reduce the activation energy of the catalyst activation, and the prepared catalyst has a higher metal activity.
[0056] In some embodiments, the weight ratio of the catalyst carrier to the active metal compound is (74-93): (25-101). The present application limits the weight ratio of the carrier to the active metal compound in the impregnation solution to obtain a loading weight of the active metal on the catalyst of 3% to 30%; for example, 5wt% to 20wt%; for example, any value among 3%, 5%, 8%, 10%, 13%, 15%, 18%, 20%, 23%, 25%, 28%, 30% or any range between two values, and the amount of the active metal is calculated as the amount of its oxide.
[0057] In some embodiments, the binder is pseudo-boehmite; the sol agent is selected from one or more of nitric acid, hydrochloric acid, acetic acid and citric acid; preferably nitric acid. The pore volume of the amorphous silica-alumina powder is 1.0-2.0 mL / g, and the specific surface area is 400-600 m 2 / g, average pore size ≥10nm; pseudo-boehmite pore volume is 0.4~1.0mL / g, specific surface area is 150~300m 2 / g, average pore size ≥9nm.
[0058] The present application uses pseudo-boehmite as a binder. After the catalyst is calcined, the binder becomes alumina. The pseudo-boehmite can be used as a binder without volatile impurities and will not affect the activity of the catalyst. At the same time, the pseudo-boehmite has the above-mentioned higher pore volume and specific surface area, and can provide high pore volume and high specific surface area together with amorphous silica-alumina. The above-mentioned proportion of amorphous silica-alumina and pseudo-boehmite are mixed to form a catalyst carrier. After calcination, the carrier strength, active metal dispersion, reaction sites, catalyst stability and catalytic reaction efficiency can be improved.
[0059] In some embodiments, the specific process of step S1 includes: kneading amorphous silicon aluminum powder, a binder and a sol agent, extruding, drying I, and calcining I to obtain a catalyst carrier;
[0060] The conditions for drying I include: a drying temperature of 100 to 300° C. and a drying time of 0.5 to 24 h; for example, a drying temperature of 150 to 200° C. and a drying time of 2 to 6 h; for example, a drying temperature of 100° C., 120° C., 150° C., 180° C., 200° C., 220° C., 250° C., 280° C., 300° C. or any range between any two thereof.
[0061] The conditions of roasting I include: a roasting temperature of 300-600°C and a roasting time of 0.5-24h; for example, a roasting temperature of 400-600°C and a roasting time of 2-6h. For example, the roasting temperature is selected from any value of 300°C, 320°C, 350°C, 380°C, 400°C, 420°C, 450°C, 480°C, 500°C, 520°C, 550°C, 580°C, 600°C or a range between any two thereof; the roasting time is selected from any value of 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h or a range between any two thereof.
[0062] The above-mentioned drying temperature, calcination temperature and time adopted in the present application can fully remove the moisture and volatile substances in the carrier so as to control the activity and stability of the catalyst, and at the same time can enhance the mechanical strength of the carrier and stabilize the catalyst. The pore structure of the carrier can also be improved by calcination, and the porosity and specific surface area can be further increased, which is helpful to improve the activity and selectivity of the catalyst. The surface of the carrier can be activated under the above-mentioned high temperature calcination to form evenly distributed active sites.
[0063] In some embodiments, the specific process of step S2 includes: impregnating the catalyst support in an impregnation solution containing an active metal compound, drying II, and calcining II to obtain a catalyst;
[0064] The conditions for drying II include: drying temperature of 100-300°C, and drying time of 0.5-24h; for example, drying temperature of 150-200°C, and drying time of 2-6h; for example, drying temperature of 100°C, 120°C, 150°C, 180°C, 200°C, 220°C, 250°C, 280°C, 300°C, or any range between any two thereof.
[0065] The conditions of roasting II include: a roasting temperature of 300-600°C and a roasting time of 0.5-24h; for example, a roasting temperature of 400-600°C and a roasting time of 2-6h. For example, the roasting temperature is selected from any value of 300°C, 320°C, 350°C, 380°C, 400°C, 420°C, 450°C, 480°C, 500°C, 520°C, 550°C, 580°C, 600°C or a range between any two thereof; the roasting time is selected from any value of 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h or a range between any two thereof.
[0066] The present application forms a catalyst by uniformly dispersing the active metal on the surface of the carrier through impregnation. This impregnation dispersion method helps to improve the activity and stability of the catalyst; the uniform distribution of the active metal can ensure sufficient contact between the reactants and the catalyst, thereby improving the efficiency of the catalytic reaction.
[0067] Under the conditions of the above-mentioned drying temperature, calcination temperature and calcination time, the present application can fully remove the moisture brought by the catalyst impregnation process, and prevent the catalyst from losing activity due to excessive moisture during use; the catalyst can also be activated at the above-mentioned calcination temperature, so that the catalyst forms an appropriate pore structure, and the specific surface area, activity and selectivity of the catalyst are improved; the active metal of the catalyst and the carrier can form a stable chemical bond, and the thermal stability and chemical stability of the catalyst can be improved; calcination at the above-mentioned temperature can remove impurities in the catalyst, etc., and improve the purity and activity of the catalyst.
[0068] In some embodiments, the activation conditions in step S3 include: hydrogen partial pressure of 0.1-8 MPa, reaction temperature of 200-600°C, and reaction time of 1-48 h; for example, hydrogen partial pressure of 0.1-1 MPa, reaction temperature of 300-500°C, and reaction time of 4-24 h. For example, hydrogen partial pressure is selected from any value of 0.1, 0.5, 1, 2, 3, 4, 5, 6, 7, 8 MPa or any range between two values; reaction temperature is selected from any value of 200, 250, 300, 350, 400, 450, 500, 550, 600°C or any range between two values; reaction time is selected from any value of 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 25, 30, 35, 40, 45, 48 h or any range between two values.
[0069] The present application selects to activate the catalyst under the above-mentioned reaction temperature and the above-mentioned hydrogen partial pressure conditions. Hydrogen can react with oxygen atoms on the surface of the catalyst to generate water to release more active sites, thereby improving the activity of the catalyst; hydrogen can also form metal hydrides with metal atoms on the surface of the catalyst, thereby stabilizing the catalyst structure and extending the service life of the catalyst; activating the catalyst in a hydrogen atmosphere can inhibit side reactions on the catalyst surface, thereby reducing the generation of by-products, increasing the yield of the target product, and improving selectivity.
[0070] According to the third aspect of the present application, there is provided the use of the above catalyst or the catalyst obtained by the above method in the hydrocracking reaction of Fischer-Tropsch wax oil.
[0071] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0072] The raw materials used in the examples of this application are all commercially available.
[0073] Example 1
[0074] Take amorphous silicon aluminum powder (pore volume 1.5mL / g, specific surface area 450m 2 / g, average pore size 13nm), pseudo-boehmite (pore volume 0.45mL / g, specific surface area 200m 2 / g, average pore size 9.2nm), add a sol agent (0.04wt% nitric acid aqueous solution) under stirring, mix well, knead into shape, and then dry it at 150°C for 2h, and calcine it at 550°C for 2h to obtain an S1 catalyst carrier; in this process, the weight ratio of amorphous silica aluminum powder, binder and sol agent is 80:20:15.
[0075] Nickel nitrate and ethylenediaminetetraacetic acid are mixed to prepare an impregnation solution, wherein the molar ratio of the metal compound Ni to ethylenediaminetetraacetic acid is 1:0.5; a hydrocracking catalyst carrier is taken and impregnated therein, the weight ratio of the catalyst carrier to the active metal compound is 81:76, the catalyst is dried at 150°C for 2h, and calcined at 500°C for 2h to prepare a catalyst S1, wherein the active metal element accounts for 15% of the catalyst weight.
[0076] The above catalyst was activated under reducing conditions, that is, at a hydrogen partial pressure of 0.1 MPa and a reaction temperature of 450° C., and reacted for 6 hours to obtain an activated catalyst S1.
[0077] Example 2
[0078] Take amorphous silicon aluminum powder (pore volume 1.5mL / g, specific surface area 450m 2 / g, average pore size 13.5nm), pseudo-boehmite (pore volume 0.45mL / g, specific surface area 200m 2 / g, average pore size 9.2nm), add a sol agent (0.03% nitric acid aqueous solution) under stirring, mix well, knead into shape, and then dry it at 150°C for 2h, and calcine it at 550°C for 2h to obtain an S2 catalyst carrier; in this process, the weight ratio of amorphous silica aluminum powder, binder and sol agent is 70:30:20.
[0079] Nickel nitrate and ethylenediaminetetraacetic acid are mixed to prepare an impregnation solution, wherein the molar ratio of the metal compound Ni to ethylenediaminetetraacetic acid is 1:0.5; a hydrocracking catalyst carrier is taken and impregnated therein, the weight ratio of the catalyst carrier to the active metal compound is 81:76, the catalyst is dried at 150°C for 2h, and calcined at 500°C for 2h to prepare a catalyst S2, wherein the active metal element accounts for 15% of the catalyst weight.
[0080] The above catalyst was activated under reducing conditions, that is, at a hydrogen partial pressure of 0.3 MPa and a reaction temperature of 450° C., and reacted for 6 hours to obtain an activated catalyst S2.
[0081] Example 3
[0082] Take amorphous silicon aluminum powder (pore volume 1.6mL / g, specific surface area 460m 2 / g, average pore size 13.2nm), pseudo-boehmite (pore volume 0.5mL / g, specific surface area 230m 2 / g, average pore size 9.4nm), add a sol agent (0.03% nitric acid aqueous solution) under stirring, mix well, knead into shape, and then dry it at 150°C for 2h, and calcine it at 550°C for 2h to obtain an S3 catalyst carrier; in this process, the weight ratio of amorphous silica aluminum powder, binder and sol agent is 65:35:18.
[0083] Nickel nitrate and citric acid are mixed to prepare an impregnation solution, wherein the molar ratio of the metal compound Ni to the citric acid is 1:0.5; a hydrocracking catalyst carrier is taken and impregnated therein, the weight ratio of the catalyst carrier to the active metal compound is 81:76, the catalyst is dried at 150°C for 2h, and calcined at 500°C for 2h to prepare a catalyst S2, wherein the active metal element accounts for 15% of the catalyst weight.
[0084] The above catalyst was activated under reducing conditions, that is, at a hydrogen partial pressure of 0.1 MPa and a reaction temperature of 450° C., and reacted for 6 hours to obtain an activated catalyst S3.
[0085] Example 4
[0086] Take amorphous silicon aluminum powder (pore volume 1.5mL / g, specific surface area 450m 2 / g, average pore size 13nm), pseudo-boehmite (pore volume 0.45mL / g, specific surface area 200m 2 / g, average pore size 9.2nm), add a sol agent (0.03% nitric acid aqueous solution) under stirring, mix well, knead into shape, and then dry it at 150°C for 2h, and calcine it at 550°C for 2h to obtain an S4 catalyst carrier; in this process, the weight ratio of amorphous silica aluminum powder, binder and sol agent is 80:20:15.
[0087] Nickel nitrate and ethylenediaminetetraacetic acid are mixed to prepare an impregnation solution, wherein the molar ratio of the metal compound Ni to ethylenediaminetetraacetic acid is 1:0.5; a hydrocracking catalyst carrier is taken and impregnated therein, the weight ratio of the catalyst carrier to the active metal compound is 81:76, the catalyst is dried at 150°C for 2h, and calcined at 500°C for 2h to prepare a catalyst S2, wherein the active metal element accounts for 15% of the catalyst weight.
[0088] The above catalyst was activated under reducing conditions, that is, at a hydrogen partial pressure of 0.1 MPa and a reaction temperature of 450° C., and reacted for 6 hours to obtain an activated catalyst S4.
[0089] Example 5
[0090] Take amorphous silicon aluminum powder (pore volume 1.5mL / g, specific surface area 450m 2 / g, average pore size 13nm), pseudo-boehmite (pore volume 0.42mL / g, specific surface area 210m 2 / g, average pore size 9nm), add sol (0.03% nitric acid aqueous solution) under stirring, mix evenly, knead and shape, and then dry at 150℃ for 2h, and calcine at 550℃ for 2h to obtain S5 catalyst carrier. In this process, the weight ratio of amorphous silicon aluminum powder, binder and sol is 80:20:15.
[0091] Nickel nitrate and ethylenediaminetetraacetic acid are mixed to prepare an impregnation solution, wherein the molar ratio of the metal compound Ni to ethylenediaminetetraacetic acid is 1:1; a hydrocracking catalyst carrier is taken and impregnated therein, the weight ratio of the catalyst carrier to the active metal compound is 94:25, the catalyst is dried at 150°C for 2h, and calcined at 500°C for 2h to prepare a catalyst S2, wherein the active metal element accounts for 5% of the catalyst weight.
[0092] The above catalyst was activated under reducing conditions, that is, at a hydrogen partial pressure of 0.1 MPa and a reaction temperature of 300° C., and reacted for 4 hours to obtain an activated catalyst S5.
[0093] Example 6
[0094] Take amorphous silicon aluminum powder (pore volume 1.3mL / g, specific surface area 400m 2 / g, average pore size 12nm), pseudo-boehmite (pore volume 0.45mL / g, specific surface area 200m 2 / g, average pore size 9.2nm), add a sol agent (0.03% nitric acid aqueous solution) under stirring, mix well, knead into shape, and then dry it at 150°C for 2h, and calcine it at 550°C for 2h to obtain an S6 catalyst carrier; in this process, the weight ratio of amorphous silica aluminum powder, binder and sol agent is 80:20:15.
[0095] Nickel nitrate and tartaric acid are mixed to form an impregnation solution, wherein the molar ratio of the metal compound Ni to tartaric acid is 1:0.8; a hydrocracking catalyst carrier is impregnated therein, the weight ratio of the catalyst carrier to the active metal compound is 87:50, the catalyst is dried at 150°C for 2h, and calcined at 500°C for 2h to prepare a catalyst S2, wherein the active metal element accounts for 10% of the catalyst weight.
[0096] The above catalyst was activated under reducing conditions, that is, at a hydrogen partial pressure of 0.1 MPa and a reaction temperature of 450° C., and reacted for 6 hours to obtain an activated catalyst S6.
[0097] Example 7
[0098] Take amorphous silicon aluminum powder (pore volume 1.4mL / g, specific surface area 430m 2 / g, average pore size 12nm), pseudo-boehmite (pore volume 0.48mL / g, specific surface area 200m2 / g, average pore size 9.5nm), add a sol agent (0.03% nitric acid aqueous solution) under stirring, mix well, knead into shape, and then dry it at 150°C for 2h, and calcine it at 500°C for 4h to obtain S7 catalyst carrier; in this process, the weight ratio of amorphous silica aluminum powder, binder and sol agent is 80:20:15.
[0099] Nickel nitrate and ethylenediaminetetraacetic acid are mixed to prepare an impregnation solution, wherein the molar ratio of the metal compound Ni to ethylenediaminetetraacetic acid is 1:0.5; a hydrocracking catalyst carrier is taken and impregnated therein, the weight ratio of the catalyst carrier to the active metal compound is 75:101, the catalyst is dried at 150°C for 2h, and calcined at 500°C for 2h to prepare a catalyst S2, wherein the active metal element accounts for 20% of the catalyst weight.
[0100] The above catalyst was activated under reducing conditions, that is, at a hydrogen partial pressure of 0.5 MPa and a reaction temperature of 400° C. for 20 h to obtain an activated catalyst S7.
[0101] Example 8
[0102] Take amorphous silicon aluminum powder (pore volume 1.5mL / g, specific surface area 450m 2 / g, average pore size 13nm), pseudo-boehmite (pore volume 0.45mL / g, specific surface area 200m 2 / g, average pore size 9.2nm), add a sol agent (0.04% nitric acid aqueous solution) under stirring, mix well, knead into shape, and then dry it at 200°C for 2h, and calcine it at 550°C for 2h to obtain an S8 catalyst carrier; in this process, the weight ratio of amorphous silica aluminum powder, binder and sol agent is 80:20:15.
[0103] Nickel nitrate and ethylenediaminetetraacetic acid are mixed to prepare an impregnation solution, wherein the molar ratio of the metal compound Ni to ethylenediaminetetraacetic acid is 1:0.5; a hydrocracking catalyst carrier is taken and impregnated therein, the weight ratio of the catalyst carrier to the active metal compound is 81:76, the catalyst is dried at 200°C for 2h, and calcined at 550°C for 2h to prepare a catalyst S1, wherein the active metal element accounts for 15% of the catalyst weight.
[0104] The above catalyst was activated under reducing conditions, that is, at a hydrogen partial pressure of 0.5 MPa and a reaction temperature of 450° C., and reacted for 6 hours to obtain an activated catalyst S8.
[0105] Example 9
[0106] Take amorphous silicon aluminum powder (pore volume 1.5mL / g, specific surface area 450m 2 / g, average pore size 13nm), pseudo-boehmite (pore volume 0.45mL / g, specific surface area 200m 2 / g, average pore size 9.2nm), add sol (0.04% nitric acid aqueous solution) under stirring, mix evenly, knead and shape, and then dry at 150℃ for 2h, and calcine at 550℃ for 2h to obtain S9 catalyst carrier. In this process, the weight ratio of amorphous silicon aluminum powder, binder and sol is 80:20:15.
[0107] Cobalt nitrate and citric acid are mixed to prepare an impregnation solution, wherein the molar ratio of Co in the metal compound to citric acid is 1:0.5; a hydrocracking catalyst carrier is taken and impregnated therein, the weight ratio of the catalyst carrier to the active metal compound is 87:51, the catalyst is dried at 150°C for 2h, and calcined at 500°C for 2h to prepare a catalyst S1, wherein the active metal element accounts for 10% of the catalyst weight.
[0108] The above catalyst was activated under reducing conditions, that is, at a hydrogen partial pressure of 0.8 MPa and a reaction temperature of 500° C., and reacted for 8 hours to obtain an activated catalyst S9.
[0109] Example 10
[0110] Take amorphous silicon aluminum powder (pore volume 1.5mL / g, specific surface area 450m 2 / g, average pore size 13nm), pseudo-boehmite (pore volume 0.45mL / g, specific surface area 200m 2 / g, average pore size 9.2nm), add a sol agent (0.04% nitric acid aqueous solution) under stirring, mix well, knead into shape, and then dry it at 150°C for 2h, and calcine it at 550°C for 2h to obtain an S10 catalyst carrier; in this process, the weight ratio of amorphous silica aluminum powder, binder and sol agent is 80:20:15.
[0111] Nickel nitrate and ethylenediaminetetraacetic acid are mixed to prepare an impregnation solution, wherein the molar ratio of the metal compound Ni to ethylenediaminetetraacetic acid is 1:0.5; a hydrocracking catalyst carrier is taken and impregnated therein, the weight ratio of the catalyst carrier to the active metal compound is 81:76, the catalyst is dried at 150°C for 2h, and calcined at 500°C for 2h to prepare a catalyst S1, wherein the active metal element accounts for 15% of the catalyst weight.
[0112] The above catalyst was activated under reducing conditions, that is, at a hydrogen partial pressure of 0.1 MPa and a reaction temperature of 550° C. for 6 hours to obtain an activated catalyst S10.
[0113] Comparative Example 1
[0114] Take amorphous silicon aluminum powder (pore volume 1.5mL / g, specific surface area 450m 2 / g, average pore size 13nm), pseudo-boehmite (pore volume 0.45mL / g, specific surface area 200m 2 / g, average pore size 9.2nm), add sol (0.04% nitric acid aqueous solution) under stirring, mix evenly, knead and shape, and then dry at 150℃ for 2h, and calcine at 550℃ for 2h to obtain D1 catalyst carrier. In this process, the weight ratio of amorphous silica-alumina powder, binder and sol is 80:20:15.
[0115] Ammonium metatungstate, nickel nitrate and ethylenediaminetetraacetic acid are mixed to prepare an impregnation solution, wherein the molar ratio of W and Ni in the metal compounds to ethylenediaminetetraacetic acid is 3:1:0.5; a hydrocracking catalyst carrier is taken and impregnated therein, the weight ratio of the catalyst carrier to the active metal compound is 65:35:30, the catalyst is dried at 150°C for 2h, and calcined at 500°C for 2h to prepare a catalyst D1, wherein the active metal element accounts for 28% of the catalyst weight.
[0116] The above catalyst was activated under reducing conditions, that is, at a hydrogen partial pressure of 0.1 MPa and a reaction temperature of 450° C. for 6 h to obtain an activated catalyst D1.
[0117] Comparative Example 2
[0118] Take amorphous silicon aluminum powder (pore volume 1.5mL / g, specific surface area 450m 2 / g, average pore size 13nm), pseudo-boehmite (pore volume 0.45mL / g, specific surface area 200m 2 / g, average pore size 9.2nm), add sol (0.04% nitric acid aqueous solution) under stirring, mix evenly, knead and shape, and then dry at 150°C for 2h, and calcine at 550°C for 2h to obtain D2 catalyst carrier. In this process, the weight ratio of amorphous silicon aluminum powder, binder and sol is 80:20:15.
[0119] Ammonium metatungstate, nickel nitrate and ethylenediaminetetraacetic acid are mixed to prepare an impregnation solution, wherein the molar ratio of W and Ni of the metal compounds to ethylenediaminetetraacetic acid is 3:1:0.5; a hydrocracking catalyst carrier is impregnated therein, the weight ratio of the catalyst carrier to the active metal compound is 65:35:30, the catalyst is dried at 150°C for 2h, and calcined at 500°C for 2h to prepare a catalyst D2, wherein the active metal element accounts for 28% of the catalyst weight.
[0120] The catalyst was activated under reducing conditions, i.e., hydrogen partial pressure of 7 MPa, reaction temperature of 360 °C, C2S space velocity of 0.1 h -1The reaction was continued for 12 h to obtain activated catalyst D2.
[0121] Comparative Example 3
[0122] Take amorphous silicon aluminum powder (pore volume 1.5mL / g, specific surface area 450m 2 / g, average pore size 13nm), pseudo-boehmite (pore volume 0.45mL / g, specific surface area 200m 2 / g, average pore size 9.2nm), add sol (0.04% nitric acid aqueous solution) under stirring, mix evenly, knead and shape, and then dry at 150°C for 2h, and calcine at 550°C for 2h to obtain D3 catalyst carrier. In this process, the weight ratio of amorphous silica-alumina powder, binder and sol is 80:20:15.
[0123] Nickel nitrate and ethylenediaminetetraacetic acid are mixed to prepare an impregnation solution, wherein the molar ratio of the metal compound Ni to ethylenediaminetetraacetic acid is 1:0.5; a hydrocracking catalyst carrier is taken and impregnated therein, the weight ratio of the catalyst carrier to the active metal compound is 68:126, the catalyst is dried at 150°C for 2h, and calcined at 500°C for 2h to prepare a catalyst D3, wherein the active metal element accounts for 25% of the catalyst weight.
[0124] The above catalyst was activated under reducing conditions, that is, at a hydrogen partial pressure of 0.1 MPa and a reaction temperature of 450° C., and reacted for 8 hours to obtain an activated catalyst D3.
[0125] Comparative Example 4
[0126] Take amorphous silicon aluminum powder (pore volume 1.5mL / g, specific surface area 450m 2 / g, average pore size 13nm), pseudo-boehmite (pore volume 0.45mL / g, specific surface area 200m 2 / g, average pore size 9.2nm), add sol (0.04% nitric acid aqueous solution) under stirring, mix evenly, knead and shape, and then dry at 150℃ for 2h, and calcine at 550℃ for 2h to obtain D4 catalyst carrier. In this process, the weight ratio of amorphous silicon aluminum powder, binder and sol is 75:25:15.
[0127] Ammonium metatungstate, nickel nitrate and ethylenediaminetetraacetic acid are mixed to prepare an impregnation solution, wherein the molar ratio of W and Ni in the metal compounds to ethylenediaminetetraacetic acid is 2.5:1:0.5; a hydrocracking catalyst carrier is taken and impregnated therein, the weight ratio of the catalyst carrier to the active metal compound is 72:32:22, the catalyst is dried at 150°C for 2h, and calcined at 500°C for 2h to prepare a catalyst D4, wherein the active metal element accounts for 22% of the catalyst weight.
[0128] The catalyst was activated under reducing conditions, i.e., hydrogen partial pressure of 7 MPa, reaction temperature of 350 °C, C2S space velocity of 0.1 h -1 The reaction was continued for 12 h to obtain activated catalyst D4.
[0129] Application Examples
[0130] The activated catalysts S1-S10 of Examples 1 to 10 and the activated catalysts D1-D4 of Comparative Examples 1 to 4 were used, and the whole fraction of the Fischer-Tropsch synthesis hydrorefining tail oil (distillation range 360-750° C.) was used as a raw material to carry out a hydrocracking reaction. The reaction was carried out on a 100 mL hydrogenation device, and the reaction conditions were: a hydrogen-to-oil ratio of 800, a reaction pressure of 7 MPa, and a volume space velocity of 1.5 h -1 , reaction temperature 365℃, and selectivity results at the same conversion rate were compared and the results are shown in Table 1.
[0131] Table 1
[0132] sample Conversion rate, % 160~360℃ selectivity, % S1 65 71 S2 65 72 S3 65 75 S4 65 72 S5 65 71 S6 65 70 S7 65 74 S8 65 73 S9 65 72 S10 65 71 D1 65 66 D2 65 72 D3 65 67 D4 65 73
[0133] It can be seen from the test data in Table 1 that the preparation method of the alkane wax oil hydrocracking / isomerization catalyst of the present application is simple, and compared with the cracking catalyst loaded with multiple active metal elements, the manufacturing cost is reduced, no sulfurization process is required, the production cost is saved, and the operational safety risk is reduced. In addition, the prepared hydrocracking catalyst has a higher selectivity for middle distillate oil, such as a selectivity of more than 70%.
[0134] Comparative Examples 1 to 4 use catalysts impregnated with two metal elements; in Comparative Examples 2 and 4, the selectivity of the middle distillate oil is close to that of Examples 1 to 10 of the present application, which indicates that the catalytic performance of the catalyst loaded with a single metal element (nickel) and activated with a hydrogen atmosphere in the hydrocracking / isomerization of alkane wax oil is comparable to that of the catalyst loaded with two metal elements (nickel and tungsten) and activated with a sulfidation process. This indicates that the use of the single active metal combined with the hydrogen activation process of the present application can achieve the effect of the dual active metal component combined with the sulfidation process, and therefore, the purpose of reducing production costs and controlling safety risks can be achieved.
[0135] Comparative Example 1 uses a catalyst impregnated with two metals and also uses a hydrogen atmosphere reduction process; under the same process conditions, the selectivity of the middle distillate oil in the reaction product catalyzed by the catalyst of Comparative Example 1 is 66%, which is 5% lower than that of Example 1; this shows that the effect of using dual active metals in Comparative Example 1 is not as good as the catalytic effect of using a single metal when using the same catalyst activation process and similar active metal amounts. Although Comparative Example 3 increases the metal loading and uses a hydrogen atmosphere to reduce the catalyst, the increase in the middle distillate oil selectivity of 67% is still not obvious.
[0136] The above description shows that the single active metal (nickel) prepared in the present application in combination with the hydrogen activation process can not only further improve the selectivity of the middle distillate oil in the hydrocracking reaction of alkane wax oil, but also save the catalyst production cost and reduce the production safety risk.
[0137] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.
[0138] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A paraffin wax oil hydrocracking / isomerization catalyst, characterized in that: The catalyst comprises a carrier and an active metal; the active metal is loaded on the inner and outer surfaces of the pores of the carrier; wherein the carrier is composed of amorphous silica-alumina and alumina; and the active metal is selected from a metal element in Group VIII.
2. The alkane wax oil hydrocracking / isomerization catalyst according to claim 1, characterized in that The active metal is cobalt or nickel; and / or, the active metal loading on the catalyst is 3 wt% to 30 wt% in terms of oxide; preferably 5 wt% to 20 wt%; And / or, the weight of the amorphous silicon aluminum is 5% to 95% of the weight of the carrier; preferably 60% to 80%; And / or, the weight of the aluminum oxide is 5% to 95% of the weight of the carrier; preferably 20% to 40%.
3. The method for preparing the alkane wax oil hydrocracking / isomerization catalyst according to claim 1 or 2, characterized in that: The method comprises the following steps: Step S1: mixing amorphous silicon aluminum powder, a binder, and a sol, drying, and calcining I to obtain a catalyst carrier; Step S2: immersing the catalyst carrier in a liquid containing an active metal compound and an organic complexing agent, drying and calcining II to obtain a catalyst; wherein the active metal element in the active metal compound is selected from a metal element in Group VIII; Step S3: activating the catalyst in a hydrogen atmosphere to obtain an active catalyst.
4. The method for preparing the alkane wax oil hydrocracking / isomerization catalyst according to claim 3, characterized in that: The weight ratio of the amorphous silica-alumina powder, the binder and the sol agent is (60-90):(20-40):(10-40); wherein the mass concentration of the sol agent is 0.01-10wt%, preferably 0.2-0.5%.
5. The method for preparing the alkane wax oil hydrocracking / isomerization catalyst according to claim 3 or 4, characterized in that: The molar ratio of the organic complexing agent to the active metal element is (0.1-2):1; and / or, the weight ratio of the catalyst support to the active metal compound is (62-96):(15-151), preferably (74-93):(25-101); And / or, the active metal element is cobalt or nickel.
6. The method for preparing a alkane wax oil hydrocracking / isomerization catalyst according to any one of claims 3 to 5, characterized in that: The amorphous silicon aluminum powder has a pore volume of 1.0 to 2.0 mL / g and a specific surface area of 400 to 600 m 2 / g, average pore size ≥10nm; And / or, the binder is pseudo-boehmite; Preferably, the pseudo-boehmite has a pore volume of 0.4 to 1.0 mL / g and a specific surface area of 150 to 300 m 2 / g, average pore size ≥9nm; and / or, the active metal compound is selected from at least one of cobalt nitrate, cobalt chloride and cobalt sulfate, or the active metal compound is selected from at least one of nickel nitrate, nickel sulfate, nickel oxide and basic nickel carbonate; and / or, the organic complexing agent is selected from at least one of ethylenediaminetetraacetic acid, citric acid, tartaric acid and lactic acid; And / or, the sol agent is selected from one or more of nitric acid, hydrochloric acid, acetic acid and citric acid; preferably nitric acid.
7. The method for preparing the alkane wax oil hydrocracking / isomerization catalyst according to any one of claims 3 to 6, characterized in that: The specific process of step S1 includes: kneading the amorphous silicon aluminum powder, the binder and the sol agent, extruding, drying I, and calcining I to obtain the catalyst carrier; Preferably, the conditions of drying I include: drying temperature of 100-300° C., and drying time of 0.5-24 h; further preferably, the drying temperature of 150-200° C., and drying time of 2-6 h; Preferably, the conditions of the calcination I include: a calcination temperature of 300 to 600° C., and a calcination time of 0.5 to 24 hours; more preferably, the calcination temperature is 400 to 600° C., and the calcination time is 2 to 6 hours.
8. The method for preparing the alkane wax oil hydrocracking / isomerization catalyst according to any one of claims 3 to 7, characterized in that: The specific process of step S2 includes: immersing the catalyst carrier in an impregnation solution containing the active metal compound, drying II, and calcining II to obtain the catalyst; Preferably, the drying conditions of II include: drying temperature of 100-300°C, drying time of 0.5-24h; further preferably, the drying temperature of 150-200°C, drying time of 2-6h; Preferably, the conditions of the calcination II include: a calcination temperature of 300-600° C., and a calcination time of 0.5-24 h; more preferably, the calcination temperature is 400-600° C., and the calcination time is 2-6 h.
9. The method for preparing the alkane wax oil hydrocracking / isomerization catalyst according to any one of claims 3 to 8, characterized in that: The activation conditions in step S3 include: hydrogen partial pressure of 0.1-8 MPa, reaction temperature of 200-600° C., and reaction time of 1-48 h; Preferably, the hydrogen partial pressure is 0.1-1 MPa, the reaction temperature is 300-500° C., and the reaction time is 4-24 h.
10. Use of the catalyst according to claim 1 or 2 or the catalyst obtained by the preparation method of the alkane wax oil hydrocracking / isomerization catalyst according to any one of claims 3 to 8 in the hydrocracking reaction of Fischer-Tropsch wax oil.